PENGARUH KUALITAS LAYANAN TERHADAP KEPUTUSANPEMBELIAN KONSUMEN DI BASEBALL FOOD COURTUNIVERSITAS NEGERI SURABAYA - CHOIRINI MARDHOTILLAH, IZZATI (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
Food and beverage industry growth is so rapid lead the competition gets tougher. Quality of service can affect the purchasing decisions of consumers towards a product, especially in services sector. Good quality care in Baseball Food Court is intended as a stimulus to the purchasing decision in Baseball Food Court, State University of Surabaya. This study attempts to explain the influence of service quality on consumer purchasing decisions in Baseball State University of Surabaya Food Court either partially or simultaneously. The population is infinite. Sampling technique is done with accidental sampling where sampling is done by chance and is not determined or planned in advance. The sample used in this research was 150 respondents. Instrument of data analysis used in this study is multiple linear regression analysis as well as questionnaire respondents as a means of data collection. Based on the resulting adjusted R2 value of 0.343 means that the quality of services influence the purchasing decisions of consumers in Baseball Food Court, State University of Surabaya by 34.3% while the remaining 65.7% is influenced by other variables outside research. The results showed that there are significant simultaneously between a lot of quality services to the purchasing decision in Baseball Food Court, State University of Surabaya. The results showed that the variable responsiveness is the most influential variables on the purchase decisions in Baseball Food Court State University of Surabaya. Keywords: Quality of Service, Purchasing Decisions